1989
DOI: 10.1111/j.1471-4159.1989.tb09176.x
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Effects of Acute Depolarization on Somatostatin Release and Protein Synthesis in Cultured Fetal and Neonatal Rat Brain Cells

Abstract: The influence of membrane depolarization on somatostatin secretion and protein synthesis by fetal and neonatal cerebrocortical neurons was studied. Cortical cells obtained by mechanical dispersion were maintained as monolayer cultures for 8 days. The ability of fetal cerebrocortical and hypothalamic cells to release immunoreactive somatostatin (IR-SRIF) was confirmed. Total protein synthesis was determined by the incorporation of [3H]phenylalanine into trichloroacetic acid-precipitable proteins. To study the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…This inhibition was completely abolished with the blockade of SS with antiserum, thus indicating that the inhibitory effect was exerted by SS. This inhibition could be due to the fact that SS secretion by fetal hypothalamic cells in this in vitro model is 10 times greater than that of GHRH (11,14).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This inhibition was completely abolished with the blockade of SS with antiserum, thus indicating that the inhibitory effect was exerted by SS. This inhibition could be due to the fact that SS secretion by fetal hypothalamic cells in this in vitro model is 10 times greater than that of GHRH (11,14).…”
Section: Discussionmentioning
confidence: 95%
“…After 5 h of incubation, defined medium was replaced by Neurobasal medium. Experiments were performed after 15 days in vitro, which is when we have observed that high levels of SS secretion and the peak of GHRH secretion occur (11,14). Medium was changed every 3-4 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of primary long-term dispersed cell cultures from fetal rat cerebral cortices was carried out as previously de scribed [22], Briefly, on the 17th day of gestation fetal Wistar rats were removed from their mother under ether anesthesia via an ab dominal incision. Cortical regions of the brain were dissected in PBS.…”
Section: Cell Culturementioning
confidence: 99%
“…In this study, we sought to investigate the effect of GRF on SS regulation by fetal rat cerebral cortical and hypothalamic cells in culture, a system previously shown to be useful in the study of neuropeptide regulation [13,[15][16][17], In contrast with previous in vitro studies, where the interactions between neuropeptides were described on a pharmacological basis, in this work we have exam ined the possible physiological role of endogenous GRF in the control of locally produced SS by adding purified anti-GRF immunoglobulins G (IgG) to cultured neurons.…”
mentioning
confidence: 99%